Metodologia para análise de investimentos em empreendimentos imobiliários com base na teoria das opções reais - Silva, Bruno Ricardo da (2019)
The application of the Real Options Theory (TOR) in the Economic Feasibility Analysis (AVE) of real estate projects aims to evaluate the value of the Management Flexibilities (FG) existing during the execution of the project. However, recent studies indicate that there is a need to develop case studies that support the feasibility of applying TOR in the real estate market. This dissertation was developed with the proposal to study the applicability of TOR in the AVE of Real Estate Investment Projects (PII), seeking to verify the contribution of the inclusion of FGs in the evaluation of the value of the project. Thus, it proposes the elaboration of a methodology to evaluate this type of development, and the application in a case study, offering support for the real estate market, thus contributing in reducing the distance between the study and the practice of TOR. The proposed methodology is divided into 3 phases. Phase 1 - Technical Characterization consists in the collection of data and information necessary and sufficient for the technical characterization and obtaining knowledge about the existing FGs in the project. Phase 2 - Economic Characterization seeks to define the components and structure the Cash Flow (CF) of the development, as well as to define the risk-free rate of return. In Phase 3 - Economic Feasibility Analysis, the risk-adjusted return rate is defined and the 4-step methodology of Copeland and Antikarov, with application of the binomial tree model, is applied to calculate the value of the FGs. The case study was developed on a project of construction of a building of 12 floors and 31 apartments for sale, expected to be delivered in 34 months, in the city of Pato Branco - PR. The FGs identified were the revision of the units price table, with the possibility of expansion or contraction in the values in each period of 6 months, from the beginning of construction. The uncertainty considered was the forecast of the number of sales of the units. The value of the options found represented 32.1% of the NPV. It was verified that the proposed methodology allowed the analysis of the value of the existing FG in the execution of an PII. The sequence of steps of the proposed methodology enabled TOR to be applied by real estate companies, contributing to reduce the distance between theory and practice of TOR application in PII.